Association of Hospital Performance Based on 30-Day Risk-Standardized Mortality Rate With Long-term Survival After Heart Failure Hospitalization: An Analysis of the Get With The Guidelines–Heart Failure Registry - Pandey, Ambarish (JAMA Cardiol, 2018)
IMPORTANCE: Among patients hospitalized with heart failure (HF), the long-term clinical implications of hospitalization at hospitals based on 30-day risk-standardized mortality rates (RSMRs) is not known. OBJECTIVE: To evaluate the association of hospital-specific 30-day RSMR with long-term survival among patients hospitalized with HF in the American Heart Association Get With The Guidelines–HF registry. DESIGN, SETTING, AND PARTICIPANTS: The longitudinal observational study included 106 304 patients with HF who were admitted to 317 centers participating in the Get With The Guidelines–HF registry from January 1, 2005, to December 31, 2013, and had Medicare-linked follow-up data. Hospital-specific 30-day RSMR was calculated using a hierarchical logistic regression model. In the model, 30-day mortality rate was a binary outcome, patient baseline characteristics were included as covariates, and the hospitals were treated as random effects. The association of 30-day RSMR-based hospital groups (low to high 30-day RSMR: quartile 1 [Q1] to Q4) with long-term (1-year, 3-year, and 5-year) mortality was assessed using adjusted Cox models. Data analysis took place from June 29, 2017, to February 19, 2018. EXPOSURES: Thirty-day RSMR for participating hospitals. MAIN OUTCOMES AND MEASURES: One-year, 3-year, and 5-year mortality rates. RESULTS: Of the 106 304 patients included in the analysis, 57 552 (54.1%) were women and 84 595 (79.6%) were white, and the median (interquartile range) age was 81 (74-87) years. The 30-day RSMR ranged from 8.6% (Q1) to 10.7% (Q4). Hospitals in the low 30-day RSMR group had greater availability of advanced HF therapies, cardiac surgery, and percutaneous coronary interventions. In the primary landmarked analyses among 30-day survivors, there was a graded inverse association between 30-day RSMR and long-term mortality (Q1 vs Q4: 5-year mortality, 73.7% vs 76.8%). In adjusted analysis, patients admitted to hospitals in the high 30-day RSMR group had 14% (95% CI, 10-18) higher relative hazards of 5-year mortality compared with those admitted to hospitals in the low 30-day RSMR group. Similar findings were observed in analyses of survival from admission, with 22% (95% CI, 18-26) higher relative hazards of 5-year mortality for patients admitted to Q4 vs Q1 hospitals. CONCLUSIONS AND RELEVANCE: Lower hospital-level 30-day RSMR is associated with greater 1-year, 3-year, and 5-year survival for patients with HF. These differences in 30-day survival continued to accrue beyond 30 days and persisted long term, suggesting that 30-day RSMR may be a useful HF performance metric to incentivize quality care and improve long-term outcomes.